Sexual behavior and its correlates after traumatic brain injury. Issue 2 (March 2015) - Turner, Daniel; Schöttle, Daniel; Krueger, Richard; Briken, Peer
Abstract : Purpose of review: Traumatic brain injury (TBI) is one of the leading causes of permanent disability in young adults and is frequently accompanied by changes in sexual behaviors. Satisfying sexuality is an important factor for overall quality of life in people with disabilities. The purpose of this article is to review the studies evaluating the assessment, correlates and management of sexuality following TBI. Recent findings: The Brain Injury Questionnaire of Sexuality is the first validated questionnaire specifically developed for adults with TBI. A considerable amount of individuals with TBI show inappropriate sexual behaviors and sexual dysfunctions. Whereas inappropriate sexual behaviors are related to younger age, less social participation and more severe injuries, sexual dysfunctions show an association with higher fatigue, higher depression scores, less self-esteem and female sex. Healthcare professionals have suggested that because of discomfort at the individual or institutional level, sexual problems are often not sufficiently addressed and have suggested that a specialist should treat sexual problems. Summary: Although some important correlates of sexual problems could be identified, methodological differences across studies limit their comparability. Furthermore, there is an absence of evidence-based treatment strategies for addressing sexual problems. Therapeutic efforts should take into account the identified correlates of sexual problems following TBI.